2015
DOI: 10.1134/s1070427215030076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nature of a ligand on electrochemical characteristic of tin films in cycling in lithium-ion batteries

Abstract: Potentiodynamic and galvanostatic cycling in 1 M ethylene carbonate-dimethyl carbonate solution of LiClO 4 were used to study electrolytic tin fi lms deposited from complex (tartrate, citrate, and citrate-trilonate) electrolytes. It was shown that the nature of a ligand strongly affects the electrochemical characteristics, specifi c capacity of tin fi lms, and effi ciency of their cycling in lithium power sources. The most stable charge-discharge characteristics are inherent in tin fi lms deposited from the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Comparison of the obtained results with the data of [14] indicates that the specific capacity of tin films obtained from pyrophosphate electrolyte is significantly higher compared to the capacity of tin films obtained from citrate-trilonate (750 mA•h•g -1 ), citrate ( 500 mA•h•g -1 ) and tartrate (400 mA•h•g -1 ) electrolytes. Higher specific characteristics of tin precipitation during lithium incorporation and extraction may be due to the difference in the mechanism of their electrolytic production.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Comparison of the obtained results with the data of [14] indicates that the specific capacity of tin films obtained from pyrophosphate electrolyte is significantly higher compared to the capacity of tin films obtained from citrate-trilonate (750 mA•h•g -1 ), citrate ( 500 mA•h•g -1 ) and tartrate (400 mA•h•g -1 ) electrolytes. Higher specific characteristics of tin precipitation during lithium incorporation and extraction may be due to the difference in the mechanism of their electrolytic production.…”
Section: Introductionmentioning
confidence: 71%
“…Earlier [14], we published the results of studies of thin tin films obtained from complex tartrate (KNatart), citrate (Na 3 citr), and citrate-trilonate (Na 3 citr/Na 2 H 2 edta) electrolytes as LIB anodes. It has been shown that the nature of the ligand determines such electrochemical characteristics as the specific capacitance value and cycling efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…surface failure and sputtering of the active substance. 2 In a previous work, 3 the electrodeposition and properties of films deposited from tartrate, citrate, and citrate-trilonate electrolytes were investigated; it was shown that the films electrodeposited from a citrate electrolyte had the best charge-discharge characteristics in lithium power sources. The efficiency of citrate solutions was also shown during the electrodeposition of Sn-Cu alloys, which have high corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%